The Influence of the Work Environment and Organizational Commitment on the Performance of the State Civil Apparatus at the Regional Education Office of North Sulawesi Province - Kyrieeleison Timothy Laloan; Wehelmina Rumawas; Leviane J. H. Lotulung (Newinera Publisher, 2024)
In an initial survey conducted at the North Sulawesi Provincial Education Office, there were several deficiencies in the work environment, including uneven internet connectivity, outdated equipment, and suboptimal room temperature conditions. This study was quantitative using a cross sectional design, involving 143 ASN with a sample of 60 people selected using a simple random sampling method. Data was collected through questionnaires and observations. The research results show that good working environmental conditions have a positive and significant influence on the performance and organizational commitment of ASN in the service. Based on these findings, it is recommended to improve facilities and infrastructure and create a conducive working atmosphere. This will support the transformation of quality education services, increasing the sense of pride and belonging among employees.